Contemporary Textile Design Creation Sourced from Visual Aesthetics of Kawung Motif Classical Batik - Wahida, Adam; M. Hendra Himawan (Mudra Jurnal Seni Budaya, 2024)
The development of contemporary art and design is a dynamic reflection of social values, technological advancements, cultural shifts, and evidence of the ever-changing nature of human expression. However, local identities are often not visible, and many works of art and design seem stereotypical with similar appearances. Based on these conditions, it is necessary to conduct research on art creation by exploring local cultural values as an identity. This article describes the process of creating contemporary textile designs sourced from the visual aesthetics of classic batik Kawung motifs, which are full of aesthetic value. The art creation method is carried out by collecting information about the visual aesthetics of classic batik Kawung motifs, exploring ideas based on visual aesthetics in Kawung batik motifs, developing creation ideas through design experiments, and realizing textile designs into fabric prototypes. The results of this study include (1) analysis of basic ornaments of geometry, repetition patterns, and symmetrical compositions in Kawung classic batik motifs, (2) the process of embodiment of contemporary textile design with the concept of transformation geometry through rotation, reflection to create rhythm and composition, as well as translation and dilatation to find the artistic value of shapes, (3) descriptions of the form of contemporary textile design works that have been produced. The study results show that classic batik's aesthetic value is a potential source of ideas for creating contemporary textile designs. Through a formalistic study of Kawung classic batik motifs, a method of making ornaments with transformative geometry techniques was found as a guideline and formulation for creating contemporary textile designs. Local values in the Kawung motif, such as the pattern of rotation, reflection, rhythm, and recomposition of geometric shapes, are still relevant and contextual with the development of the times. Thus, it is essential to use it as a source of inspiration for creating contemporary textile designs with a strong identity.